A Study on the Effect of Quaternization of Polyene Antibiotics’ Structures on Their Activity, Toxicity, and Impact on Membrane Models - Olga Omelchuk; Anna Tevyashova; Svetlana Efimova; Natalia Grammatikova; Elena Bychkova; George Zatonsky; Lyubov Dezhenkova; Nikita Savin; Svetlana Solovieva; Olga Ostroumova; Andrey Shchekotikhin (Antibiotics, 2024)
Polyene antibiotics have been used in antifungal therapy since the mid-twentieth century. They are highly valued for their broad spectrum of activity and the rarity of pathogen resistance to their action. However, their use in the treatment of systemic mycoses often results in serious side-effects. Recently, there has been a renewed interest in the development of new antifungal drugs based on polyenes, particularly due to the emergence of highly dangerous pathogenic strains of fungi, such as Candida auris, and the increased incidence of mucormycosis. Considerable understanding has been established regarding the structure–biological activity relationships of polyene antifungals. Yet, no previous studies have examined the effect of introducing quaternized fragments into their molecular structure. In this study, we present a series of amides of amphotericin B, nystatin, and natamycin bearing a quaternized group in the side chain, and discuss their biological properties: antifungal activity, cytotoxicity, and effects on lipid bilayers that mimic fungal and mammalian cell membranes. Our research findings suggest that the nature of the introduced quaternized residue plays a more significant role than merely the introduction of a constant positive charge. Among the tested polyenes, derivatives 4b, 5b, and 6b, which contain a fragment of N-methyl-4-(aminomethyl)pyridinium in their structure, are particularly noteworthy due to their biological activity.